Supportive Relationship Between Teachers And Students And Among Peers - Stefa, Enkeleda (European Journal of Multidisciplinary Studies, 2018)
This study highlights the importance how a positive environment at class and school affects the relationship between teachers and students and among peers. The positive spirit in a classroom is a determining component for creating a favorable learning environment. Various studies have come to the conclusion that students learn better in an environment, both supported by teachers and other students. Positive relationships provide support, motivation, and better performance for school students. Besides that, improving students’ relationships with teachers has a significant, positive and long-lasting impact on students’ social and scholastic development. Different studies have shown that students who experience close, positive, and supportive relationships with their teachers have higher levels of achievements compared to other students who have experienced more conflicting relationships. Primary, secondary and high school students make greater efforts if they learn in environments where teachers and peers support is not lacking. Students of all ages, especially teenagers, are very much influenced by their peers. According to the motivational perspective, positive relationships between students help their engagement towards school, because they meet their needs for belonging and the connection with the environment, nourish positive feelings, important for the good functioning of the individual and their role as students. Support grows a sense of motivation and leads the student towards school success. Peers’ support affects motivational elements as self-confidence and academic achievement and significantly affects an effective engagement.